Standardized High Versus Low Dose Cranberry Proanthocyanidin Extracts for Prevention of Urinary Tract Infection Confirmed by Pyuria in Women: A Randomized Clinical Trial. (29th May 2020) - Leblanc, Vicky; Babar, Asma; Moore, Lyne; Dudonné, Stéphanie; Desjardins, Yves; Lemieux, Simone; Bochard, Valérie; Guyonnet, Denis; Howell, Amy; Dodin, Sylvie
Abstract: Objectives: Cranberry products are often used by women to prevent urinary tract infections (UTIs) but literature regarding their efficacy remains discordant. The clinical efficacy of cranberry products for prevention of UTIs in healthy women could be increased by 1) using an optimal dose of cranberry extract standardized in proanthocyanidins (PACs); 2) adequate measure of compliance. The objective of this randomized clinical trial was to assess the efficacy of an optimal dose of cranberry extract standardized in PACs for the prevention of recurrent UTI confirmed by pyuria during a 24-week intervention period. Methods: One hundred and forty-five women with a history of recurrent UTI in the past 12 months were randomized to receive a dose of cranberry extract Urophenol™, standardized in PACs (2 × 18.5 mg PACs daily, n  = 72) or a control dose (2 × 1 mg PACs daily, n  = 73) for a 24-week period. Women were asked to contact the study coordinator if they presented symptoms of UTI and to provide a urine sample to evaluate the diagnosis by confirmation of pyuria. Since some women were unable to provide a urine sample in the presence of UTI symptoms, regression analyses were performed with two different approaches, 1) symptomatic UTI episodes without a urine sample were considered as no symptomatic UTIs with pyuria; 2) symptomatic UTI episodes without a urine sample were considered as symptomatic UTIs with pyuria. Analyses were adjusted for age. Results: No significant differences in the number of symptomatic UTI with pyuria were found between groups during the 24-week intervention period in intention to treat analyses using either approach (approach 1: incidence rate ratio 0.98, 95% CI 0.57–1.68; approach 2: 0.86, 95% CI 0.56–1.32). Among women who experienced less than 5 UTIs in the year preceding enrolment, daily consumption of 2 × 18.5 mg PACs was associated with a decrease in the number of symptomatic UTIs compared to the control dose (approach 1: incidence rate ratio 0.65, 95% CI 0.31–1.37; approach 2: 0.54, 95% CI 0.30–0.99). Compliance to capsule intake was higher than 90% in both groups. Conclusions: In women who experience less than 5 UTIs in the last year, daily consumption of a standardized dose of 2 × 18.5 mg PACs could have a preventative impact on the incidence of symptomatic UTIs confirmed by pyuria. Funding Sources: Supported by Diana Foods and MAPAQ.